Pengaruh risiko bisnis dan tata kelola perusahaan terhadap skor tingkat kesehatan bank pada bank swasta nasional devisa di Indonesia - Mi Razul Amrullah; Herizon Herizon (STIE Perbanas Surabaya, 2018)
The purpose of research was to determine whether the credit risk, market risk, liquidity risk. Operational risk and GCG simultaneously and partially towards the bank’s soundness. The population of this research is the national private commercial banks in Indonesia and they were taken by using a purposive sampling. The research sample consists of Bank Central Asia, CIMB Niaga Bank, Bank Danamon Indonesia, Bank PAN Indonesia (Panin Bank), Bank OCBC NISP, Bank May Bank Indonesia, Bank Mega, Bank Bukopin and Bank ICBC Indonesia. The data were analysed using multiple linear regression analysis. The results of the study show that credit risk, market risk, liquidity risk. Operational risk and GCG simultaneously have a signifi cant infl uence. Partially credit risk, market risk, liquidity risk and GCG have insignifi cant infl uence, while operational risk has a signifi cant effect on the soundness of Nasionaol private commercial banks in Indonesia.